2009
DOI: 10.1021/bi901503g
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into Substrate Specificity and the anti β-Elimination Mechanism of Pectate Lyase

Abstract: Pectate lyases harness anti beta-elimination chemistry to cleave the alpha-1,4 linkage in the homogalacturonan region of plant cell wall pectin. We have studied the binding of five pectic oligosaccharides to Bacillus subtilis pectate lyase in crystals of the inactive enzyme in which the catalytic base is substituted with alanine (R279A). We discover that the three central subsites (-1, +1, and +2) have a profound preference for galacturonate but that the distal subsites can accommodate methylated galacturonate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 49 publications
(65 reference statements)
1
69
0
Order By: Relevance
“…This observation suggests that there is more conformational flexibility within the active site of YePL2A than YeOGL and that the active site of YeOGL presents another strong example of the structural convergence of the ␤-elimination machinery in pectate lyases. The potential role of this highly conserved arginine in catalytic proton transfer to the glycosidic oxygen of the scissile bond, in YeOGL and other pectate lyases, remains to be established (42,45).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation suggests that there is more conformational flexibility within the active site of YePL2A than YeOGL and that the active site of YeOGL presents another strong example of the structural convergence of the ␤-elimination machinery in pectate lyases. The potential role of this highly conserved arginine in catalytic proton transfer to the glycosidic oxygen of the scissile bond, in YeOGL and other pectate lyases, remains to be established (42,45).…”
Section: Resultsmentioning
confidence: 99%
“…Abstraction occurs via general base attack by an arginine (family 1, 2, 3, and 10) or lysine (family 9) (43), the high pK a of these residues accounting for the basic pH optima observed across the PL landscape. Recently, the contributions of an ancillary lysine in family 1 PLs and asparagines in family 9 have been proposed to influence the catalytic rate by stabilizing the enolate-enolate intermediate (45). These residues have been implicated in hydrogen donation and/or bonding to the nascent oxyanion of the uronate group following electron transfer to the transient double bond between C5 and C6.…”
Section: Methodsmentioning
confidence: 99%
“…S3A); the corresponding gene is renamed "vexL." Pectate lyases degrade acidic polymers, such as pectin, from plant tissues (18), and the α-1,4-linked polygalacturonic acid backbone structure of pectin superficially resembles Vi antigen. Purified A. denitrificans VexL enzyme depolymerized Vi antigen (Fig.…”
Section: −8mentioning
confidence: 99%
“…Oligosaccharides modified by one or more O-acetyl groups (δ m/z = 42.011) were also present. Lyase enzymes cleave polysaccharides through an eliminative mechanism and create a characteristic (anhydro) 4-deoxy-α-D-galact-4-enuronosyl residue at the nonreducing end of the oligosaccharide (18). This modification was evident in MS/MS fragmentation products (Fig.…”
Section: −8mentioning
confidence: 99%
“…It was suggested that the PL1 lyase generates an enol-enolate through donation of a proton by a nearby Lys to one of the oxygen atoms of the carboxylate. The authors suggest that through this intermediate, PL1 lyases are more active than PL10 and PL9 enzymes that can only generate the enolateenolate intermediate (Seyedarabi et al, 2010).…”
Section: Pectin Degradationmentioning
confidence: 99%